Econometric Analysis of Effects of Nitrogenous Fertilizer Usage on Tomato Yield in Tokat, Turkey - Bilge Gözener; Oğuz Parlakay (Turkish Journal of Agriculture: Food Science and Technology)
This study aims to investigate the effects of nitrogen fertilizer application on tomato yield by using econometric models. The data obtained by questionnaire from 53 farmers who produce tomatoes in Tokat province constitute the main material of the study. The Simple Random Sampling Method was used to determine the sample size with a 90% confidence interval and 10% margin of error. Nine models were tried to determine the best model to explain the effect of nitrogenous fertilizer usage in tomato cultivation. The data in the models were used to calculate the growers’ optimal fertilizer amount of use (physical optimum and economical optimum values were calculated) and the results were compared to the ones suggested by the experts. As a result, through the statistical studies, quadratic model was found to be the most suitable one. It has been determined that tomato farmers use less (10.54 kg da-1) or excess (23.48 kg da-1) N fertilizer than the level at which economic optimum is achieved.